The replacement of fish meal with fermented soya bean meal or soya bean meal in the diet of Pacific white shrimp (Litopenaeus vannamei). (4th March 2020) - Yao, Wenxiang; Zhang, Chunyan; Li, Xiaoqin; He, Ming; Wang, Jing; Leng, Xiangjun
Abstract: The present study evaluated the effects of replacing fish meal (FM) with soya bean meal (SM) or fermented soya bean meal (FSM) on growth, nutrient utilization, digestive enzyme activity and intestinal histology of Pacific white shrimp. The basal diet (control) contained 18% FM, and then, FM in basal diet was replaced by 1/6 (17%), 1/3 (33%) and 1/2 (50%) by the inclusion of SM and FSM, referring to SM17, SM33, SM50, FSM17, FSM33 and FSM50 respectively. The shrimp (3.0 g) were fed one of the seven diets for 8 weeks. The results showed that the control group had the highest weight gain (WG) (653.8%) and the lowest feed conversion ratio (FCR) (1.61). SM33, SM50 and FSM50 groups showed significantly lower WG, crude protein (CP) digestibility, hepatopancreatic protease, amylase activity and higher FCR than the control ( p  < .05). The villi height of SM33, SM50 and FSM50 groups and the intestinal wall thickness of SM groups and FSM50 group were significantly lower than those of the control ( p  < .05). In conclusion, fish meal (18%) in white shrimp diet could be replaced by 1/6 (17%) and 1/3 (33%) with SM and FSM respectively. Fermented soya bean meal could replace more fish meal than soya bean meal did.